Strengthening English Speaking Skills Through Reading Instructions For Employees Of Pt Capsugel Indonesia - Supriatnoko, Supriatnoko; Hasyim, Nur; Priambodo, Sujiwo; Edel, Eky Erlanda; Abdillah , Taufik Eryadi (Green Publisher Indonesia, 2025)
This community service program was conducted at PT Capsugel Indonesia to address the need for improving employees’ English skills, particularly in reading technical instructions and orally conveying them. Such skills are essential for supporting customer service and preparing employees to meet global workplace challenges. The program adopted a Service Learning (SL) approach, integrating the roles of lecturers and students in assisting the community. Training was carried out over two days through lectures, discussions, practice, and simulations, covering activities such as reading aloud, understanding written instructions, guided conversations, and interview preparation. A total of 52 employees participated, with evaluation based on pretest–post-test and speaking practice. The results indicated significant improvement, with the average pretest score of 63.6 rising to 86.9 in the post-test, an increase of 23.3 points (from C+ to A). The paired conversation evaluation yielded an average score of 80.3 (A-), showing strength in fluency and pronunciation, but weaknesses in vocabulary, interaction, and confidence. Partner satisfaction questionnaires, completed by 52 respondents, revealed that 97.2% agreed the program was beneficial. Overall, this training successfully enhanced employees’ reading and speaking skills in English while strengthening their preparedness for competitive workplace demands.